Udział w wystąpieniach wolnościowych jako przesłanka uznania za osobę represjonowaną z powodów politycznych w orzecznictwie sądów administracyjnych - Janiak, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The subject of the analysis is the regulations of the Act of 20 March 2015 on anti-communist opposition activists and persons repressed for political reasons, which relate to the possibility for an individual to obtain the status of a person repressed for political reasons due to his or her participation in the period from 1 January 1956 to 31 July 1990 in opposition activities for the regaining of Poland’s independence and sovereignty or respect for political human rights in Poland. The main method of research was the empirical research method, which consisted in the analysis of the jurisprudence of the voivodship administrative courts and the Supreme Administrative Court in Poland, and its aim was to discern how these courts interpreted the legal regulations under analysis. In the initial period of their application, the divergences in the jurisprudence concerned the possibility of recognising record materials in the resources of the Institute of National Remembrance as documents created with the participation of the applicant within the meaning of Article 4 of the Act. Currently, this issue is not in doubt, which is the result of a normative change. An issue that is not uniformly understood in the jurisprudence of the courts is the distribution of the burden of proof in the proceedings conducted by the Head of the Office for War Veterans and Victims of Oppression in which a decision is issued confirming the status of a repressed person.
Keywords: osoba represjonowana; wystąpienie wolnościowe; postępowanie administracyjne; Szef Urzędu ds. Kombatantów i Osób Represjonowanych; Prezes Instytutu Pamięci Narodowej